Dynamic Instability Analysis of a Rotating Ship Shaft under a Periodic Axial Force by Discrete Singular Convolution - Wei Li; Zhiwei Song; Xuexia Gao; Zhigang Chen (Shock and Vibration)
Dynamic instability of a rotating ship shaft subjected to a periodic axial force is studied by using discrete singular convolution (DSC) with regularized Shannon’s delta kernel. The excitation frequency is related to the spinning speed and the number of blades on the propeller. Effects of number of blades, constant term in the periodic force, and damping on dynamic instability regions are investigated. The results have shown that the increase of number of blades and damping could improve the dynamic stability of rotating shaft with damping. The increase of constant term in the periodic force leads to dynamic instability regions shifting to lower frequencies, making the shaft more sensitive to periodic force. Those dynamic instability regions obtained by DSC method have been compared with those by Floquet’s method to verify the application of DSC method to dynamic instability analysis of rotating ship shaft.